PERILAKU HARGA DALAM PEMASARAN BAWANG MERAH DI DAERAH ISTIMEWA YOGYAKARTA - Sugiharti Mulya Handayani (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2004)
The research conducted to identity the influence of seasonality in production of Onio price, identity long run dynamic equilibrium of onion price and analyze pricing behavior and market performance of onion. the data used in the study were mostly secondary (time sries) quarterly for 1996 until 2000.